DESAIN UI/UX WEBSITE SALON TREATMENT ANYA SKINCARE - yuniar adi widya astuti; Henny Lukitasari, Evelyne; Khoirul Anwar, Ahmad (JURNAL KEMADHA, 2024)
Women can beautify their appearance by making a beauty salon a solution to get a more attractive appearance. One of them is Salon Treatment Anya Skincare. It is one of the beauty businesses in Sukabumi. The type of treatment is only facial treatment. Currently, Salon Treatment Anya Skincare is experiencing problems in arranging treatment schedules. This is due to the limited of workers and only accepting 2-4 customers per day. However, the customers are more than 4 people. The solution is to create media of a User Interface (UI) User Experience (UX) website to make orders through the website such as reservations. On the website, it can also buy available skincare products. The design method is qualitative by collecting data at the location and interviewing informants from the Anya Skincare salon. The results of this design are the UI/UX website as the main media to support the Anya Skincare salon in arranging visiting hours and purchasing skincare products online.